Revising psychosocial aspects of the nursing work - Manetti, Marcela Luísa; Marziale, Maria Helena Palucci; Robazzi, Maria Lúcia do Carmo Cruz (Rev Rene, 2008)
The psychosocial aspects on nursing working environment have called attention because of the increasing number of absenteeism and the health problems of nursing professionals, leading to damages on the quality of assistance care. The objective of this research was to identify the psychosocial aspects on nursing working environment and to analyze the consequences that they cause to the workers and services. We deal with a systematized review of a literature from 1995 to 2005, of published researches in index journals on national and international databases. On the studied period 49 articles were published about the psychosocial aspects on nursing working environment focusing on restructuring and innovations in the work organization, autonomy, work climate, professional growth possibility, management style, interpersonal relationship and violence. The consequences of the exposition are stress, low level of job satisfaction, physical-mental distress, suffering, absenteeism and turn over. The results obtained in this study collaborate with planning and implantation of preventive programs to occupational illness.